A study on factors that affecting on employees’ job satisfaction among employees in safety and health industry / Mohammad Amirul Afiq Mohammad - Mohammad, Mohammad Amirul Afiq (Faculty of Business and Management, 2016)
Among all the assets of an organization, employee is the most significant and precious asset which is essential for healthy operation of all other resources of the organization. So, when employee is satisfied in terms of their jobs, then only productivity level goes up. It is because Lease (1998) said that “Employees who have higher job satisfaction are usually less absent, less likely to leave, more productive, more likely to display organizational commitment and more likely to be satisfied with their lives”. Otherwise in today’s liberalized world there are lots of opportunities present in the job market for the right candidate. The primary objective of this study is to assess the level job satisfaction among employees in safety and health industry overall job satisfaction. Then, the next objective of this study is also to examine the relationship between factors that affecting on employee’s job satisfaction. The factors are pay and compensation, supervision, co-worker, promotion and work itself. The sampling size is 65 respondents. Results indicate that employees in safety and health industry are at high level of job satisfaction. Moreover, the job satisfaction in safety and health industry only has significant relationship with supervision, co-worker, promotion and work itself.